APPLIED ANATOMY OF PRANVAHSROTAS W.S.R TO CARDIOPULMONARY SYSTEM - Dabral Preeti (International Journal of Ayurveda and Pharma Research, 2020)
Srotas are the channel in the body through which various substances pass from one place to another. There are an infinite number of Srotas present in the body. All the physiological and pathological processes conducted in the body are dependent on Srotas. Pranvahasrotas are the most important Srotas in the body which is the pathway for Pranswaropivayu or we can say oxygen. Pranvahasrotas transport oxygen to all over the body and our life is dependent on oxygen. Like Pranvahsrotas, in contemporary science cardiopulmonary system transport oxygen. Pranavaha Srotas has its two Moolsthan from where it is regulated. Cardiopulmonary system is consists of two interdependent system. One is Respiratory System which is involved in transfer of oxygen to blood and make it oxygenated and cardiovascular system is responsible to carry it all over the body. Since heart and its entities and lungs are the principal organ of the cardiopulmonary system. Function, sign and symptoms of Pranvahasrotas and cardiopulmonary system has many similarities. Objective of the study is comprehensive study of anatomical feature of Pranvahsrotasmool in Ayurved to cardiopulmonary system in contemporary science.